2018
DOI: 10.1371/journal.pgen.1007650
|View full text |Cite
|
Sign up to set email alerts
|

Detecting past and ongoing natural selection among ethnically Tibetan women at high altitude in Nepal

Abstract: Adaptive evolution in humans has rarely been characterized for its whole set of components, i.e. selective pressure, adaptive phenotype, beneficial alleles and realized fitness differential. We combined approaches for detecting polygenic adaptations and for mapping the genetic bases of physiological and fertility phenotypes in approximately 1000 indigenous ethnically Tibetan women from Nepal, adapted to high altitude. The results of genome-wide association analyses and tests for polygenic adaptations showed ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 95 publications
1
44
0
Order By: Relevance
“…While some coding-region changes have been identified in Tibetan humans [9,16] and goats [31] and Andean humans [41], the majority of SNPs have been identified in non-coding regions, suggesting that gene regulation is affected. Additionally, few studies have attempted to identify genome-wide associations between genotype and phenotype [3,10] and only a handful of physiological studies have been conducted in domesticated populations, making it challenging to show convergence in genetic changes and their effects across species. It is also possible that selection is not acting on the physiological traits being measured (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some coding-region changes have been identified in Tibetan humans [9,16] and goats [31] and Andean humans [41], the majority of SNPs have been identified in non-coding regions, suggesting that gene regulation is affected. Additionally, few studies have attempted to identify genome-wide associations between genotype and phenotype [3,10] and only a handful of physiological studies have been conducted in domesticated populations, making it challenging to show convergence in genetic changes and their effects across species. It is also possible that selection is not acting on the physiological traits being measured (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…3000–4500 m), Tibetans have a high resting ventilation but low arterial oxygen content and low oxygen saturation—of the three populations who have lived at high altitudes for generations, they are the most hypoxic [2]. There is a correlation in women between higher levels of oxygen saturation and an increased number of surviving children, and alleles undergoing positive selection are associated with more positive pregnancy outcomes in Tibetan women [3], suggesting that selection is still acting on this population. Some Tibetans show an increase in haemoglobin concentration, but only at altitudes higher than 4000 m [2].…”
Section: High-altitude Adaptationsmentioning
confidence: 99%
“…Genome scans of polymorphisms have detected strong selective sweep signals in Tibetans at 2 loci, EGLIN1 and EPAS 1 (4, 5). However, a recent study of Tibetans found no clear evidence for polygenic adaptation for low hemoglobin concentration (2), questioning whether hemoglobin concentration is truly the target of selection, or merely a consequence or component of the true adaptive trait, as proposed previously (6). The study of Jeong et al (2) found polygenic adaptation for a lower heart rate in Tibetan females that was also associated with greater reproductive success (2).…”
mentioning
confidence: 89%
“…Hemoglobin concentration is a defining feature in the differential manifestations of adaptation between high-altitude Andeans and Tibetans (1). Tibetans demonstrate a hemoglobin concentration that would be comparable to sea level residents (1); the lower concentration is associated with greater reproductive success (2) and exercise capacity (3). Genome scans of polymorphisms have detected strong selective sweep signals in Tibetans at 2 loci, EGLIN1 and EPAS 1 (4, 5).…”
mentioning
confidence: 99%
“…2010 ; Hernandez et al. 2011 ; Schrider and Kern 2017 ), as well as in high-altitude adaptation of Himalayan populations ( Jeong and Di Rienzo 2014 ; Jeong et al. 2018 ).…”
Section: Introductionmentioning
confidence: 99%